Implications of deconstruction for teaching and learning of reading - Santana, Manoela Oliveira de Souza (2012)
This article addresses the implications of deconstruction for teaching and learning of reading, before concerns about how to establish the construction of meaning in the act of reading. To this end, discussions shall be made regarding conceptions of reading under various theoretical and methodological approaches, discussing reading now as decoding, or as cognitive processing or as interaction, as well as treating yourself to the deconstruction and its problematization in this activity with a view in language teaching more proficient as the proposed OCEM - Curriculum Guidelines for Secondary Education - languages, Codes and their Technologies (2008). The approach will be made, as a review of theoretical constructs in the light of Arrojo (2003), Derrida (2008), Carvalho (2002), CORACINI (1995), Koch (2007), Figueredo and Jesus (2006). The focus of discourse pervades this production by the fact that the construction of meaning is a possibility of the economy mean between the necessary and impossible, decentering the notion of meaning as fixed, linear left by the author in his text, to be achieved by the reader.